Uganda : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper describes Uganda's experience under the 2013 Policy Support Instrument (PSI). The current 2013 PSI was approved by the IMF's Executive Board in June 2013 with an initial duration of three years. Overall, performance under this PSI has been assessed to be satisfactory. Most quantitative assessment criteria were met, and macroeconomic stability maintained. However, the pace of structural reforms slowed down compared with the past, and only about half of the structural benchmarks were ultimately met. The experience shows the importance of ensuring commitment to the reforms, explaining them better, and getting broad-based buy-in to achieve progress.